Pendekatan Kebijakan Negara dalam Memerangi Penggelapan Uang: Perspektif Politik Hukum - Muhammad Wildan Ichsandi; Ariawan Gunadi; Indah Siti Aprilia; Juan Matheus (Jurnal Hukum Lex Generalis, 2024)
This research aims to examine the implementation of government policies and the role of legal politics in preventing and combating the crime of money embezzlement. The research method employed is juridical-normative through literature study using statutory and conceptual approaches, with deductive data analysis. The discussion results indicate that law serves a dual function: preventing through norms and sanctions, and prosecuting perpetrators, with the evidentiary focus on malicious intent and the impact of the actions. Combating money embezzlement requires a combination of penal (repressive law enforcement) and non-penal (preventive measures) approaches. Non-penal efforts encompass environmental improvements, legal education, raising public awareness, and securing potential crime targets. Government criminal policy, as part of broader social policy, is manifested through legal socialization by authorities, case analysis, and coordination among institutions and with community leaders. Although penal measures have shown results, their effectiveness still faces challenges such as slow investigations and sophisticated perpetrator methods, making the integration of non-penal strategies crucial. In conclusion, addressing money embezzlement demands firm and comprehensive law enforcement, synergistically integrating penal and non-penal approaches to achieve optimal prevention and control effectiveness.